2015
DOI: 10.1186/s13017-015-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization of open abdomen in critically ill surgical patients

Abstract: IntroductionThis study was designed to describe the time-course and microbiology of colonization of open abdomen in critically ill surgical patients and to study its association with morbidity, mortality and specific complications of open abdomen. A retrospective cohort analysis was done.MethodsOne hundred eleven consecutive patients undergoing vacuum-assisted closure with mesh as temporary abdominal closure method for open abdomen were analyzed. Microbiological samples from the open abdomen were collected. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Surgery was not a statistically significant factor associated with isolation of Candida. These findings were lower compared to a previous study where Candida were observed in 33% of the colonized patients confirming the vulnerability of the critically ill surgical patients to fungal infections (Rasilainen, Juhani, & Kalevi, 2015). The observed difference could be due to the kind of patients selected.…”
Section: Surgical Interventionscontrasting
confidence: 55%
“…Surgery was not a statistically significant factor associated with isolation of Candida. These findings were lower compared to a previous study where Candida were observed in 33% of the colonized patients confirming the vulnerability of the critically ill surgical patients to fungal infections (Rasilainen, Juhani, & Kalevi, 2015). The observed difference could be due to the kind of patients selected.…”
Section: Surgical Interventionscontrasting
confidence: 55%
“…Often the OA, particularly if prolonged, results in fascia retraction and consequently in large abdominal wall defects that require complex abdominal wall reconstruction. Moreover, the situation is often complicated by a contaminated field [ 121 ] with high risk of infections and wound complications, such as wound infections, seromas, fistula formation, recurrence of the defect, and mortality [ 122 124 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, leaving the abdomen open for a longer period increases the risk of microbial colonization of the wound. But this has not been shown to increase wound complications or enterocutaneous fistula formation [69].…”
Section: Clinical Management Of Patients With Open Abdomenmentioning
confidence: 99%